Ground state ferromagnetism in a generalized Hubbard model with strong correlations - Didukh, L.; Kramar, O. (Condensed Matter Physics, 2003)
The present paper considers the ground state ferromagnetic ordering in a generalized Hubbard model with correlated hopping and interatomic exchange interaction in the case of strong correlations at non-integer band filling. The quasi-particle energy spectrum is obtained by means of a generalized mean-field approximation. The ground state energy of the system and the condition of ferromagnetic state realization are calculated. The dependences of magnetization on energy parameters and band-filling are obtained.